1990
DOI: 10.1002/app.1990.070390315
|View full text |Cite
|
Sign up to set email alerts
|

Elastic behavior of natural rubber filled vulcanizates

Abstract: SynopsisThe reinforcement effect of carbon black and, the effect of accelerator-to-sulfur ratio variation on the elastic behavior of natural rubber vulcanizates have been studied. The Mooney-Rivlin relation was used to describe the behavior of the rubber matrix, and values of constants c1 and c, have been evaluated with the use of the strain-amplification factor. The stress softening of the vulcanizates tested has also been examined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1997
1997
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 9 publications
0
8
0
Order By: Relevance
“…These values are tabulated in Table III. The constant C 1 describes the behavior predicted by the statistical theory of rubberlike elasticity, and its value is directly proportional to the number of network chains per unit of volume of the rubber 37. The value of C 2 determines the number of steric obstructions and the number of effectively trapped elastic entanglements as well as other network defects 38.…”
Section: Resultsmentioning
confidence: 99%
“…These values are tabulated in Table III. The constant C 1 describes the behavior predicted by the statistical theory of rubberlike elasticity, and its value is directly proportional to the number of network chains per unit of volume of the rubber 37. The value of C 2 determines the number of steric obstructions and the number of effectively trapped elastic entanglements as well as other network defects 38.…”
Section: Resultsmentioning
confidence: 99%
“…decrease of the total (physical and chemical) crosslink density. 5,16 Finally, the variation of the calculated Mooney constants and upon IIR addition is represented by 2C 1 2C 2 the ratio presented in Table 2, owing to the fact C 2 /C 1 that the attachment between rubber molecules and carbon black particles makes a contribution to the nature of the interphase bonding of the rubber network,6 acting as a physical crosslink.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been published describing the mechanism by which carbon black reinforces elastomers,1,2 the deformation mechanisms of Ðlled elastomers due to the state of cure and the particle size of a given Ðller,3 the dependence of hysteresis on carbon black loading4 and the elastic behaviour of Ðlled elastomer vulcanizates. 5 An important aspect of the structure of a rubber blend is the nature of the interphase bonding.6 During blending of natural rubber (NR) and styreneÈbutadiene rubber (SBR) Ðlled vulcanizate, the bond between NR and carbon black is quite weak and it has been found that carbon continues to migrate in the SBR phase7. Transfer of a portion of the carbon black from one phase to another would lower its modulus proportionately more than the increase in modulus of the phase with higher carbon black concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The constant C 1 describes the behavior predicted by the statistical theory of rubber-like elasticity, and its value is directly proportional to the number of network chains per unit volume of the rubber [20]. The value of C 2 determines the number of steric obstructions and the number of effectively trapped elastic entanglements as well as other network defects [21].…”
Section: Figures 3(a) and (B) Show The Experimental Stress-strain Curmentioning
confidence: 99%